The Spatial Dependence in Central Sulawesi Province - Ladjin, Nurjanna; Suman, Agus; Devanto, Devanto; Kresna, Rachmad (Opción, 2019)
This study aims to analyze the role of spatial dependence on income conver- gence based on data from 13 regency/municipality in the province of Central Sulawesi in the period 2007-2017. The analysis used in this research is ex- ploratory spatial data analysis and spatial durbin model. The results of the study did not find a positive spatial spillover on the income convergence of 13 regency / municipality in the province of Central Sulawesi and clusterization of PDRB per capita resulting in two spatial regimes. Local government as the policy maker needs to utilize the absence of spatial spillover on the regional economic growth shown by this study to consider their programs to increase the regional economic growth and reduce the income gap between regions.